Dimensional structure of first episode psychosis. Issue 6 (15th January 2019) - Tonna, Matteo; Ossola, Paolo; Marchesi, Carlo; Bettini, Elena; Lasalvia, Antonio; Bonetto, Chiara; Lenzi, Jacopo; Rucci, Paola; Iozzino, Laura; Cellini, Massimo; Comacchio, Carla; Cristofalo, Doriana; et al.
Abstract : Aim: Current diagnostic systems, DSM‐5 and ICD‐10, still adopt a categorical approach to classify psychotic disorders. The present study was aimed at investigating the structure of psychotic symptomatology in both affective and non‐affective psychosis from a dimensional approach. Methods: Participants with a first episode psychosis (FEP) were recruited from a cluster‐randomized controlled trial (GET‐UP PIANO TRIAL), offered to all Community Mental Health Centres (CMHCs) located across two northern Italian regions. After clinical stabilization, patients were assessed with a comprehensive set of psychopathological measures including the Positive and Negative Syndrome Scale, the Hamilton Depression Rating Scale and the Bech‐Rafaelsen Mania Rating Scale. A two‐step cluster analysis was performed. Results: Overall, 257 FEP patients (male, n = 171, 66.5%; mean age = 24.96 ± 4.56) were included in the study. The cluster analysis revealed a robust four‐cluster solution: delusional‐persecutory (n = 82; 31.9%), depressed (n = 95; 37%), excited (n = 26; 10.1%) and negative‐disorganized (n = 54; 21%), thus suggesting a quadripartite structure with both affective and non‐affective dimensions. Among non‐affective dimensions, negative and disorganization symptoms constituted a unique construct apart from positive symptoms. Conclusions: Symptom dimensions may represent a useful tool for dissecting the indistinct and non‐specific psychopathology of FEP in order to better target specific interventions.